The Role of School Libraries as Teaching and Learning Resources - Tridana, Anggi; Vlora, Rani Kurnia (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
A library is a work unit of an institution that contains a collection of books to support increasing learning resources that are arranged to be read, studied and used as reference materials. It is impossible for an educational institution to run well if the teachers and students are not supported by the learning resources needed to carry out teaching and learning activities. The purpose of this research is to look at the role of the library as a teaching and learning resource for students and teaching staff at SMPN 2 South Pemulutan. The research method used is descriptive research with a case study type that will be carried out on the role of the library at SMPN 2 South Pemulutan as a source of teaching and learning in schools. Data collection techniques through observation, interviews and documentation. The informants in this research were library users at SMPN 2 South Pemulutan, namely students, and teachers or education staff. The results of the research state that the SMPN 2 South Pemulutan Library has an important role as an institution that provides knowledge and information to its parent institution and its user community. The SMPN 2 Pemulutan Selatan library facilitates students and teachers or education staff (GTK) with services at the library. Teaching and learning activities are also often carried out in the library of SMPN 2 Pemulutan Selatan. There are several teaching staff who use the library as a means for